A Framework for K-12 Science Education: Practices, Crosscutting Concepts, and Core Ideas - National Research Council (The National Academies Press, 2012)
Science, engineering, and technology permeate nearly every facet of modern life and hold the key to solving many of humanity's most pressing current and future challenges. The United States' position in the global economy is declining, in part because U.S. workers lack fundamental knowledge in these fields. To address the critical issues of U.S. competitiveness and to better prepare the workforce, A Framework for K-12 Science Education proposes a new approach to K-12 science education that will capture students' interest and provide them with the necessary foundational knowledge in the field.
Keywords: Education

Advancing the Framework for Assessing Causality of Health and Welfare Effects to Inform National Ambient Air Quality Standard Reviews - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As part of its responsibilities under the Clean Air Act, the U.S. Environmental Protection Agency sets National Ambient Air Quality Standards (NAAQS) for the air pollutants carbon monoxide, lead, oxides of nitrogen, particulate matter, ozone, and sulfur dioxide. EPA uses a "weight of evidence approach" to evaluate evidence from scientific studies and describe the causal relationships between these "criteria pollutants" and any adverse impacts on human health and on public welfare - including impacts on wildlife, water, forests, agriculture, and climate. The evaluation, called an Integrated Science Assessment, is used to inform standards setting associated with the criteria pollutants. This report, produced at the request of EPA, describes EPAs and several other frameworks for inferring causality of health or welfare effects and the characteristics of evidence useful for forming a causal determination. The report concludes that EPAs causal framework is effective, reliable, and scientifically defensible, provided that key scientific questions are identified and a range of necessary expertise is engaged. More transparency in how EPA integrates evidence could improve confidence in their determinations, and more guidance is needed in the framework on how evidence should be examined for vulnerable groups (e.g., human sub-populations) and sensitive ecosystems or species.
Keywords: Environment and Environmental Studies

Greenhouse Gas Emissions Information for Decision Making: A Framework Going Forward - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Climate change, driven by increases in human-produced greenhouse gases and particles (collectively referred to as GHGs), is the most serious environmental issue facing society. The need to reduce GHGs has become urgent as heat waves, heavy rain events, and other impacts of climate change have become more frequent and severe. Since the Paris Agreement was adopted in 2015, more than 136 countries, accounting for about 80% of total global GHG emissions, have committed to achieving net-zero emissions by 2050. A growing number of cities, regional governments, and industries have also made pledges to reduce emissions. Providing decision makers with useful, accurate, and trusted GHG emissions information is a crucial part of this effort. This report examines existing and emerging approaches used to generate and evaluate GHG emissions information at global to local scales. The report develops a framework for evaluating GHG emissions information to support and guide policy makers about its use in decision making. The framework identifies six criteria or pillars that can be used to evaluate and improve GHG emissions information: usability and timeliness, information transparency, evaluation and validation, completeness, inclusivity, and communication. The report recommends creating a coordinated repository or clearinghouse to operationalize the six pillars, for example, by providing timely, transparent, traceable information; standardized data formats; and governance mechanisms that are coordinated, trusted, and inclusive of the global community.
Keywords: Environment and Environmental Studies

A Framework for Assessing Effects of the Food System - Institute of Medicine; National Research Council (The National Academies Press, 2015)
How we produce and consume food has a bigger impact on Americans' well-being than any other human activity. The food industry is the largest sector of our economy; food touches everything from our health to the environment, climate change, economic inequality, and the federal budget. From the earliest developments of agriculture, a major goal has been to attain sufficient foods that provide the energy and the nutrients needed for a healthy, active life. Over time, food production, processing, marketing, and consumption have evolved and become highly complex. The challenges of improving the food system in the 21st century will require systemic approaches that take full account of social, economic, ecological, and evolutionary factors. Policy or business interventions involving a segment of the food system often have consequences beyond the original issue the intervention was meant to address. A Framework for Assessing Effects of the Food System develops an analytical framework for assessing effects associated with the ways in which food is grown, processed, distributed, marketed, retailed, and consumed in the United States. The framework will allow users to recognize effects across the full food system, consider all domains and dimensions of effects, account for systems dynamics and complexities, and choose appropriate methods for analysis. This report provides example applications of the framework based on complex questions that are currently under debate: consumption of a healthy and safe diet, food security, animal welfare, and preserving the environment and its resources. A Framework for Assessing Effects of the Food System describes the U.S. food system and provides a brief history of its evolution into the current system. This report identifies some of the real and potential implications of the current system in terms of its health, environmental, and socioeconomic effects along with a sense for the complexities of the system, potential metrics, and some of the data needs that are required to assess the effects. The overview of the food system and the framework described in this report will be an essential resource for decision makers, researchers, and others to examine the possible impacts of alternative policies or agricultural or food processing practices.
Keywords: Food and Nutrition; Agriculture

Including Health in Global Frameworks for Development, Wealth, and Climate Change: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Including Health in Global Frameworks for Development, Wealth, and Climate Change is the summary of a three-part public webinar convened by the Institute of Medicine Roundtable on Environmental Health Sciences, Research, and Medicine and its collaborative on Global Environmental Health and Sustainable Development. Presenters and participants discussed the role of health in measuring a country's wealth (going beyond gross domestic product), health scenario communication, and international health goals and indicators. The workshop focused on fostering discussion across academic, government, business, and civil society sectors to make use of existing data and information that can be adapted to track progress of global sustainable development and human health. This report examines frameworks for global development goals and connections to health indicators, the role for health in the context of novel sustainable economic frameworks that go beyond gross domestic product, and scenarios to project climate change impacts.
Keywords: Health and Medicine

A Decision Framework for Interventions to Increase the Persistence and Resilience of Coral Reefs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Coral reefs are critical to ocean and human life because they provide food, living area, storm protection, tourism income, and more. However, human-induced stressors, such as overfishing, sediment, pollution, and habitat destruction have threatened ocean ecosystems globally for decades. In the face of climate change, these ecosystems now face an array of unfamiliar challenges due to destructive rises in ocean temperature, acidity and sea level. These factors lead to an increased frequency of bleaching events, hindered growth, and a decreasing rate of calcification. Research on interventions to combat these relatively new stressors and a reevaluation of longstanding interventions is necessary to understand and protect coral reefs in this changing climate. Previous research on these methods prompts further questions regarding the decision making process for site-specific interventions.
Keywords: Earth Sciences

Climate Change Education in Formal Settings, K-14: A Workshop Summary - National Research Council (The National Academies Press, 2012)
Climate change is occurring, is very likely caused by human activities, and poses significant risks for a broad range of human and natural systems. Each additional ton of greenhouse gases emitted commits us to further change and greater risks. In the judgment of the Committee on America's Climate Choices, the environmental, economic, and humanitarian risks of climate change indicate a pressing need for substantial action to limit the magnitude of climate change and to prepare to adapt to its impacts. A principal message from the recent National Research Council report, America's Climate Choices, this brief summary of how climate change will shape many aspects of life in the foreseeable future emphasizes the vital importance of preparation for these changes.
Keywords: Earth Sciences; Education

Incorporating the Costs and Benefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change—Guidebook - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Extreme weather events and a changing climate increasingly boost costs to transportation agencies and to the traveling public. While Departments of Transportation (DOTs) are taking into account changing climate and extreme weather when making infrastructure decisions, they typically are not using a formal set of tools or cost-benefit analyses (CBAs) to address climate resilience because they may be too time-consuming and expensive to conduct routinely.The TRB National Cooperative Highway Research Program's NCHRP Research Report 938: Incorporating the Costs and Benefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change—Guidebook was developed to try to fill the gaps identified by DOTs. It is intended to provide a consolidated resource for transportation practitioners to be able to more readily consider CBAs as a tool in their investment-decision making processes when considering different climate and extreme weather adaptation alternatives.This report has additional resources, including a web-only document NCHRP Web-Only Document 271: Guidelines to Incorporate the Costs andBenefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change, a Power Point presentation that describes the research and the results, a spreadsheet tool that provides an approximate test to see if it would be cost-effective to upgrade assets to the future conditions posed by climate change, and a spreadsheet tool that uses existing conditions without climate change only to calculate the new return period for future conditions with climate change.
Keywords: Transportation and Infrastructure

Reckoning with the U.S. Role in Global Ocean Plastic Waste - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
An estimated 8 million metric tons (MMT) of plastic waste enters the world's ocean each year - the equivalent of dumping a garbage truck of plastic waste into the ocean every minute. Plastic waste is now found in almost every marine habitat, from the ocean surface to deep sea sediments to the ocean's vast mid-water region, as well as the Great Lakes. This report responds to a request in the bipartisan Save Our Seas 2.0 Act for a scientific synthesis of the role of the United States both in contributing to and responding to global ocean plastic waste. The United States is a major producer of plastics and in 2016, generated more plastic waste by weight and per capita than any other nation. Although the U.S. solid waste management system is advanced, it is not sufficient to deter leakage into the environment. Reckoning with the U.S. Role in Global Ocean Plastic Waste calls for a national strategy by the end of 2022 to reduce the nation's contribution to global ocean plastic waste at every step - from production to its entry into the environment - including by substantially reducing U.S. solid waste generation. This report also recommends a nationally-coordinated and expanded monitoring system to track plastic pollution in order to understand the scales and sources of U.S. plastic waste, set reduction and management priorities, and measure progress.
Keywords: Environment and Environmental Studies

Tracking Alternative Jet Fuel - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB’s Airport Cooperative Research Program (ACRP) Research Report 165: Tracking Alternative Jet Fuel provides guidance to airports on ways to track alternative jet fuels. As alternative jet fuels start to enter the supply chain, there may be a need to keep track of such fuel for technical, regulatory, and commercial reasons. In addition to the guidance, a greenhouse gas calculator and an alternative fuels inventory tracking spreadsheet compare different types of tracking mechanisms and evaluate their advantages and disadvantages, impediments to implementation, and potential impacts.Spreadsheet disclaimer: This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Accelerating Decarbonization in the United States: Technology, Policy, and Societal Dimensions - Transportation Research Board; National Academy of Engineering; National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Addressing climate change is essential and possible, and it offers a host of benefits - from better public health to new economic opportunities. The United States has a historic opportunity to lead the way in decarbonization by transforming its current energy system to one with net-zero emissions of carbon dioxide. Recent legislation has set the nation on the path to reach its goal of net zero by 2050 in order to avoid the worst consequences of climate change. However, even if implemented as designed, current policy will get the United States only part of the way to its net-zero goal. Accelerating Decarbonization in the United States provides a comprehensive set of actionable recommendations to help policymakers achieve a just and equitable energy transition over the next decade and beyond, including policy, technology, and societal dimensions. This report addresses federal and subnational policy needs to overcome implementation barriers and gaps with a focus on energy justice, workforce development, public health, and public engagement. The report also presents a suite of recommendations for the electricity, transportation, built environment, industrial, fossil fuels, land use, and finance sectors.
Keywords: Environment and Environmental Studies; Earth Sciences

Forest Health and Biotechnology: Possibilities and Considerations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The American chestnut, whitebark pine, and several species of ash in the eastern United States are just a few of the North American tree species that have been functionally lost or are in jeopardy of being lost due to outbreaks of pathogens and insect pests. New pressures in this century are putting even more trees at risk. Expanded human mobility and global trade are providing pathways for the introduction of nonnative pests for which native tree species may lack resistance. At the same time, climate change is extending the geographic range of both native and nonnative pest species. Biotechnology has the potential to help mitigate threats to North American forests from insects and pathogens through the introduction of pest-resistant traits to forest trees. However, challenges remain: the genetic mechanisms that underlie trees' resistance to pests are poorly understood; the complexity of tree genomes makes incorporating genetic changes a slow and difficult task; and there is a lack of information on the effects of releasing new genotypes into the environment. Forest Health and Biotechnology examines the potential use of biotechnology for mitigating threats to forest tree health and identifies the ecological, economic, and social implications of deploying biotechnology in forests. This report also develops a research agenda to address knowledge gaps about the application of the technology.
Keywords: Environment and Environmental Studies; Biology and Life Sciences

Sustaining Ocean Observations to Understand Future Changes in Earth's Climate - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The ocean is an integral component of the Earth's climate system. It covers about 70% of the Earth's surface and acts as its primary reservoir of heat and carbon, absorbing over 90% of the surplus heat and about 30% of the carbon dioxide associated with human activities, and receiving close to 100% of fresh water lost from land ice. With the accumulation of greenhouse gases in the atmosphere, notably carbon dioxide from fossil fuel combustion, the Earth's climate is now changing more rapidly than at any time since the advent of human societies. Society will increasingly face complex decisions about how to mitigate the adverse impacts of climate change such as droughts, sea-level rise, ocean acidification, species loss, changes to growing seasons, and stronger and possibly more frequent storms. Observations play a foundational role in documenting the state and variability of components of the climate system and facilitating climate prediction and scenario development. Regular and consistent collection of ocean observations over decades to centuries would monitor the Earth's main reservoirs of heat, carbon dioxide, and water and provides a critical record of long-term change and variability over multiple time scales. Sustained high-quality observations are also needed to test and improve climate models, which provide insights into the future climate system. Sustaining Ocean Observations to Understand Future Changes in Earth's Climate considers processes for identifying priority ocean observations that will improve understanding of the Earth's climate processes, and the challenges associated with sustaining these observations over long timeframes.
Keywords: Earth Sciences

Guidelines to Incorporate the Costs and Benefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Cost-benefit analysis (CBA) is useful for climate change response and adaptation, and if used properly, it has great potential for long-range planning. CBA should help agencies navigate the spectrum of decisions from mitigation and greenhouse gas reduction to adaptation: where does investing public funds generate the most public good?The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 271: Guidelines to Incorporate the Costs and Benefits of Adaptation Measures in Preparation for Extreme Weather Events and Climate Change is published as a companion document to NCHRP Research Report 938. It includes two frameworks that were developed for the project to allow practitioners to conduct CBAs to a level of detail they deem appropriate; a sketch-level analysis can serve as a screening tool to evaluate if adaptation is even appropriate, while a more detailed climate resilience analysis can help to answer the question, “How much can I spend on an adaptation project and have it remain cost-effective?”
Keywords: Transportation and Infrastructure

A Review of the Draft 2013 National Climate Assessment - National Research Council (The National Academies Press, 2013)
As mandated by the Global Change Research Act (GCRA), the U.S. Global Change Research Program is currently producing a "National Climate Assessment" (NCA). The NCA is a report to inform the President, the Congress, and the American people about the current state of scientific knowledge regarding climate change effects on U.S. regions and key sectors, now and in the coming decades. This document contains an evaluation of the draft NCA report, presented through consensus responses to the Panel's Task Statement questions, and through a large collection of individual Panel member comments and suggestions for specific chapters, statements, figures, etc. While focusing primarily on practical suggestions for immediately improving the current draft, the Panel also raises some broader considerations about fundamental approaches used in certain parts of the NCA report, and about the scope of USGCRP research that underlies the NCA findings. Some suggestions can be viewed as longer-term advice for future versions of NCA work. This NCA has been a significantly more ambitious effort than previous assessments, in terms of the scope of topics addressed and the breadth of public engagement processes involved. Some of the important new areas include the use of "traceable accounts," the articulation of needs for future research and a vision for an ongoing assessment process, the outreach efforts to help various stakeholders define their climate-related information needs, and the initial (though incomplete) effort to assess the current state of climate change response activities around the nation. Given the current state of the science and the scope of resources available, we believe the NCA did a reasonable job of fulfilling its charge overall. Although more needs to be done to fully meet the nation's needs for information and guidance, such needs cannot be met without an expanded research effort on the part of the USGCRP and future assessments. The Panel suggests that the NCA report would be improved by addressing the numerous specific problems and concerns and the more cross-cutting issues raised in the consensus answers to the Task Statement questions—which include, for instance, the need to: 1. provide a clear overarching framework for the report that helps readers understand climate change as part of a complex system with interacting physical, biological, and human social/economic dimensions, and offers practical guidance on using iterative risk management strategies to make decisions in the face of large uncertainties; 2. clearly acknowledge how climate change affects and is affected by other types of major global environmental changes and other societal developments; 3. offer an explicit discussion about the uncertainties associated with the regional model projections presented in the NCA draft; 4. take full advantage of the e-book format planned for this document through strategic use of hyperlinks among different parts of the report and other innovative approaches that help guide the experience of the NCA's diverse audiences. As the nation continues to engage with the threats, opportunities, and surprises of climate change in its many manifestations, the 2013 NCA should prove to be a valuable resource, as a summary of the state of knowledge about climate change and its implications for the American people.
Keywords: Earth Sciences; Behavioral and Social Sciences; Environment and Environmental Studies

America's Climate Choices - National Research Council (The National Academies Press, 2011)
Climate change is occurring. It is very likely caused by the emission of greenhouse gases from human activities, and poses significant risks for a range of human and natural systems. And these emissions continue to increase, which will result in further change and greater risks. America's Climate Choices makes the case that the environmental, economic, and humanitarian risks posed by climate change indicate a pressing need for substantial action now to limit the magnitude of climate change and to prepare for adapting to its impacts. Although there is some uncertainty about future risk, acting now will reduce the risks posed by climate change and the pressure to make larger, more rapid, and potentially more expensive reductions later. Most actions taken to reduce vulnerability to climate change impacts are common sense investments that will offer protection against natural climate variations and extreme events. In addition, crucial investment decisions made now about equipment and infrastructure can "lock in" commitments to greenhouse gas emissions for decades to come. Finally, while it may be possible to scale back or reverse many responses to climate change, it is difficult or impossible to "undo" climate change, once manifested. Current efforts of local, state, and private-sector actors are important, but not likely to yield progress comparable to what could be achieved with the addition of strong federal policies that establish coherent national goals and incentives, and that promote strong U.S. engagement in international-level response efforts. The inherent complexities and uncertainties of climate change are best met by applying an iterative risk management framework and making efforts to significantly reduce greenhouse gas emissions; prepare for adapting to impacts; invest in scientific research, technology development, and information systems; and facilitate engagement between scientific and technical experts and the many types of stakeholders making America's climate choices.
Keywords: Environment and Environmental Studies; Earth Sciences

Integrating Resilience Concepts and Strategies into Transportation Planning: A Guide (The National Academies Press, 2023)
Transportation systems are increasingly vulnerable to natural and human-generated risks caused by factors such as extreme weather events and conditions, cyberattacks, pandemics, and other unanticipated events. NCHRP Research Report 1052: Integrating Resilience Concepts and Strategies into Transportation Planning: A Guide, from TRB's National Cooperative Highway Research Program, provides planning and policy professionals with six key building blocks to successfully integrate resiliency into transportation planning policy, analysis, and decision-making. Supplemental to the report are an executive summary, a contractor’s final report detailing the conduct of research, and a flier and slides for presenting the research.
Keywords: Transportation and Infrastructure

A Research Review of Interventions to Increase the Persistence and Resilience of Coral Reefs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Coral reef declines have been recorded for all major tropical ocean basins since the 1980s, averaging approximately 30-50% reductions in reef cover globally. These losses are a result of numerous problems, including habitat destruction, pollution, overfishing, disease, and climate change. Greenhouse gas emissions and the associated increases in ocean temperature and carbon dioxide (CO2) concentrations have been implicated in increased reports of coral bleaching, disease outbreaks, and ocean acidification (OA). For the hundreds of millions of people who depend on reefs for food or livelihoods, the thousands of communities that depend on reefs for wave protection, the people whose cultural practices are tied to reef resources, and the many economies that depend on reefs for fisheries or tourism, the health and maintenance of this major global ecosystem is crucial.
Keywords: Earth Sciences

Transitioning Toward Sustainability: Advancing the Scientific Foundation: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In 1999 the National Academies of Sciences, Engineering, and Medicine released a landmark report, Our Common Journey: A Transition toward Sustainability, which attempted to “reinvigorate the essential strategic connections between scientific research, technological development, and societies’ efforts to achieve environmentally sustainable improvements in human well-being.”1 The report emphasized the need for place-based and systems approaches to sustainability, proposed a research strategy for using scientific and technical knowledge to better inform the field, and highlighted a number of priorities for actions that could contribute to a sustainable future.
Keywords: Environment and Environmental Studies

Climate Change Adaptation Planning: Risk Assessment for Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB's Airport Cooperative Research Program (ACRP) Report 147: Climate Change Adaptation Planning: Risk Assessment for Airports provides guidance for practitioners to understand the specific impacts climate change may have on their airports. The guidebook may help practitioners develop adaptation actions and incorporate those actions into the airport’s planning processes.Accompanying the guidebook, an electronic assessment tool called Airport Climate Risk Operational Screening (ACROS) is enclosed as a CD-ROM. The tool uses a formula to compute an estimated level of risk for assets and operations at the airport. These airport-specific risks are then ranked to provide an enterprise-level estimate of the relative risk posed by each asset and operation.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure